Students’ perceptions towards instructor-developed screencasts as a stand-alone method of instruction on WhatsApp in an introductory statistics course during COVID-19 - Delport, D. H. (South African Journal of Higher Education, 2022)
E-learning and access to internet facilities remain a problem for many students in South Africa. The purpose of this article is to assess students’ perceptions of the use of WhatsApp as an online learning technology together with instructor-developed screencasts as a stand-alone method of instruction in an introductory statistics course during the COVID-19 pandemic at a South African university. The responses to an open-ended questionnaire showed that students preferred WhatsApp over the university’s student learning platform. Although it is advocated to use screencasts to supplement traditional lectures, the findings of this research revealed that instructor-developed screencasts have the potential to be used as a stand-alone method of instruction for the teaching and learning of introductory statistics. Participants’ responses also revealed that, apart from the electronic connection they had on WhatsApp, they valued the emotional connection as well. The sharing, support, love, as well as cooperation among the lecturer and students emphasised the importance of ubuntu in educational settings. Furthermore, the results revealed that the attitude and support of a lecturer play a crucial role in providing an online atmosphere where students feel safe and comfortable, especially during the pandemic period.